Mitochondrial dynamics modulate the expression of pro‐inflammatory mediators in microglial cells. (29th July 2013) - Park, Junghyung; Choi, Hoonsung; Min, Ju‐Sik; Park, Sun‐Ji; Kim, Jung‐Hak; Park, Hyo‐Jin; Kim, Bokyung; Chae, Jung‐Il; Yim, Mijung; Lee, Dong‐Seok
Abstract Over‐activation of microglia cells in the brain contributes to neurodegenerative processes promoted by the production of various neurotoxic factors including pro‐inflammatory cytokines and nitric oxide. Recently, accumulating evidence has suggested that mitochondrial dynamics are an important constituent of cellular quality control and function. However, the role of mitochondrial dynamics in microglial activation is still largely unknown. In this study, we determined whether mitochondrial dynamics are associated with the production of pro‐inflammatory mediators in lipopolysaccharide (LPS)‐stimulated immortalization of murine microglial cells (BV‐2) by a v‐raf/v‐myc carrying retrovirus (J2). Excessive mitochondrial fission was observed in lentivirus‐transfected BV‐2 cells stably expressing DsRed2‐mito following LPS stimulation. Furthermore, mitochondrial localization of dynamin‐related protein 1 (Drp1) (a key regulator of mitochondrial fission) was increased and accompanied by de‐phosphorylation of Ser637 in Drp1. Interestingly, inhibition of LPS‐induced mitochondrial fission and reactive oxygen species (ROS) generation by Mdivi‐1 and Drp1 knock‐down attenuated the production of pro‐inflammatory mediators via reduced nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) and mitogen‐activated protein kinase (MAPK) signaling. Our results demonstrated for the first time that mitochondrial fission regulates mitochondrial ROS production in activated microglial cells and influences the expression of pro‐inflammatory mediators through the activation of NF‐κB and MAPK. We therefore suggest that mitochondrial dynamics may be essential for understanding pro‐inflammatory mediator expression in activated microglial cells. This could represent a new therapeutic approach for preventing neurodegenerative diseases. <boxed-text content-type="graphic" id="jnc12361-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> LPS induced excessive mitochondrial fission through mitochondrial localization of de‐phosphorylation of Ser637 Drp1. Interestingly, inhibition of LPS‐induced mitochondrial fission and mitochondrial ROS generation by Mdivi‐1 and Drp1 shRNA attenuate the production of pro‐inflammatory mediators via reduced NF‐κB and MAPK signaling. Our results suggest that mitochondrial dynamics may be essential for understanding pro‐inflammatory mediator expression in activated microglial cells.